2009
DOI: 10.4161/cc.8.12.8745
|View full text |Cite
|
Sign up to set email alerts
|

Expression of indoleamine 2,3-dioxygenase in metastatic malignant melanoma recruits regulatory T cells to avoid immune detection and affects survival

Abstract: The mechanism by which malignant melanoma (MM) cells survive in lymph nodes is poorly understood. One possible mechanism by which MM cells can escape immune surveillance is through upregulation of immunomodulatory enzymes such as indoleamine 2,3-dioxygenase (IDO). In this study, 25 cases of MM lymph node metastases from patients with long and short survival were evaluated for expression of IDO and the number of Forkhead box p3 (FOXP3)-expressing regulatory T cells. Moderate to strong cytoplasmic IDO expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 29 publications
(36 reference statements)
6
135
2
2
Order By: Relevance
“…Mature myeloid DCs are the most frequently cited (15)(16)(17), but IDO1 expression has also been reported in plasmacytoid DCs, immature DCs, and macrophages (18)(19)(20). Several studies have shown that IDO1 þ cells were enriched in melanoma-draining lymph nodes (18,(21)(22)(23). Some studies also reported a correlation between high IDO1 expression in TDLN and poor clinical outcome of melanoma, suggesting that IDO1 contributes to immune evasion (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Mature myeloid DCs are the most frequently cited (15)(16)(17), but IDO1 expression has also been reported in plasmacytoid DCs, immature DCs, and macrophages (18)(19)(20). Several studies have shown that IDO1 þ cells were enriched in melanoma-draining lymph nodes (18,(21)(22)(23). Some studies also reported a correlation between high IDO1 expression in TDLN and poor clinical outcome of melanoma, suggesting that IDO1 contributes to immune evasion (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…An increased proportion of Ki67 + Tregs has been detected in multiple types of tumors, demonstrating their highly proliferative potential [30,48]. Finally, the upregulation of IDO in melanoma lymph node metastases has been associated with increased amounts of TITregs [49]. Accordingly, IDO expression by antigen-presenting cells (APCs) has been reported to directly activate Tregs and promote their proliferation [50,51].…”
Section: Mechanisms Of Intratumoral Treg Accumulationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] CD4 + CD25 + Treg cells are present in malignant effusions and blood 3,4,10 of individuals with various types of cancer, and suppress nonspecific T cell responses in vitro. Curiel and colleagues reported that Treg cells from ovarian carcinoma patients express functional CCR4 and traffic into tumor mass in response to chemokine CCL22 that is produced by tumor cells and microenvironmental macrophages.…”
Section: Introductionmentioning
confidence: 99%